Antisense Oligonucleotide-Mediated Terminal Intron Retention of the SMN2 Transcript - Loren L. Flynn; Chalermchai Mitrpant; Ianthe L. Pitout; Sue Fletcher; Steve D. Wilton (Elsevier, 2018)
The severe childhood disease spinal muscular atrophy (SMA) arises from the homozygous loss of the survival motor neuron 1 gene (SMN1). A homologous gene potentially encoding an identical protein, SMN2 can partially compensate for the loss of SMN1; however, the exclusion of a critical exon in the coding region during mRNA maturation results in insufficient levels of functional protein. The rate of transcription is known to influence the alternative splicing of gene transcripts, with a fast transcription rate correlating to an increase in alternative splicing. Conversely, a slower transcription rate is more likely to result in the inclusion of all exons in the transcript. Targeting SMN2 with antisense oligonucleotides to influence the processing of terminal exon 8 could be a way to slow transcription and induce the inclusion of exon 7. Interestingly, following oligomer treatment of SMA patient fibroblasts, we observed the inclusion of exon 7, as well as intron 7, in the transcript. Because the normal termination codon is located in exon 7, this exon/intron 7-SMN2 transcript should encode the normal protein and only carry a longer 3' UTR. Further studies showed the extra 3' UTR length contained a number of regulatory motifs that modify transcript and protein regulation, leading to translational repression of SMN. Although unlikely to provide therapeutic benefit for SMA patients, this novel technique for gene regulation could provide another avenue for the repression of undesirable gene expression in a variety of other diseases.